2010
DOI: 10.1021/ic100929f
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Removal of Sulfate, Phosphate, Arsenate, Tetrachloromercurate, and Chromate in Aqueous Solution by Means of an Activated Carbon Functionalized with a Pyrimidine-Based Anion Receptor (HL). Crystal Structures of [H3L(HgCl4)]·H2O and [H3L(HgBr4)]·H2O Showing Anion−π Interactions

Abstract: Binding of anions of great environmental concern such as SO(4)(2-), PO(4)(3-), AsO(4)(3-), HgCl(4)(2-), and CrO(4)(2-) by the protonated forms of a tren-like (tren = tris(2-aminoethyl)amine) ligand (HL) functionalized with a pyrimidine residue was studied by means of potentiometric measurements and isothermal titration calorimetry (ITC) affording log K, ΔH°, and TΔS° values for the formation of the relevant complexes. The complexes show high to very high stability due to the particular topology and electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 66 publications
2
48
0
Order By: Relevance
“…2). 11,17,18 In particular, the H 4 L[Co(CN) 6 ] complex showed one of the strongest anion-p interactions so far reported. 17 While in H 3 L 2+ protonation involves the two primary amine groups of the tren moiety, in H 4 L 3+ also the pyrimidine nitroso group is protonated.…”
Section: Anion Complexation By Hl and L1mentioning
confidence: 96%
See 1 more Smart Citation
“…2). 11,17,18 In particular, the H 4 L[Co(CN) 6 ] complex showed one of the strongest anion-p interactions so far reported. 17 While in H 3 L 2+ protonation involves the two primary amine groups of the tren moiety, in H 4 L 3+ also the pyrimidine nitroso group is protonated.…”
Section: Anion Complexation By Hl and L1mentioning
confidence: 96%
“…11,24 AC is a graphitized activated carbon with a surface area of 1062 m 2 g À1 and containing oxygen as the only heteroatom component present in signicant amount (3.9%). 11,24 Most of the surface area (ca. 1000 m 2 g À1 ) is associated to narrow micropores (diameter < 2.5-3.0 nm) whereas the remaining area corresponds to mesopores (2.5-3 nm < diameter > 50 nm) and macropores (diameter > 50 nm).…”
Section: Adsorption Studiesmentioning
confidence: 99%
“…The surface charge density (Q in mmol of protons/g of adsorbent) of the materials was determined by a method based on potentiometric titration data [44][45][46], following a reported procedure [28,30] and by using KOH 0.1 M as titrating agent. The proton isotherms were then obtained by plotting Q vs the equilibrium pHs.…”
Section: Characterization Of the Adsorbentsmentioning
confidence: 99%
“…For this reason, the control of the surface chemical functionalization of ACs without changing their textural properties [23] becomes a main objective in order to obtain efficient and selective carbon materials for metal ion recovery. We have reported a functionalization method of carbon materials [24][25][26][27][28][29][30] materials [31]. The procedure results in carbon/receptor hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a basic site corresponding to pK a = 7.02 on a low-functionalized activated carbon was considered as arene centers (Cπ site). 43 On the other hand, a theoretical calculation suggested that pK a of pyrones varied in a large interval (0−12). 39 The pK a values of basic sites obtained in this manuscript fall in the range of the basic strength mentioned above and could deepen the understanding of the versatility of the strength of basic sites on biochar surfaces.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%